Стоянка Іскорость та її місце в кам'яній добі України: історіографічний і типолого-технологічний аспекти - Науменко, О.О.; Радієвська, Т.М. (Археологія, 2022)
Статтю присвячено комплексному вивченню матеріалів зі стоянки Іскорость (Житомирська обл.) із
зібрання НМІУ, відкритої В. Хвойкою в 1911 р. Висвітлено історію досліджень пам’ятки, охарактеризовано типологічні й типолого-технологічні аспекти крем’яного інвентарю, а також розглянуто проблему культурно-хронологічної атрибуції стоянки. The Palaeolithic legacy of V. Khvoika consists of three discovered and researched sites: Kyiv-Kyrylivska, Protasiv Yar (Kyiv),
and Iskorost (Korosten, Zhytomyr Oblast). The Kyiv-Kyrylivska site gained the most publicity due to the large excavation area,
clear and more understandable stratigraphy, and the representativeness of the collection of stone and bone inventory. The site of
Iskorost was discovered in 1911 during the excavations of medieval barrows. The site has not been considered comprehensively,
despite numerous attempts to clarify the cultural and chronological context through the study of stratigraphy. In this paper, the
authors try to fill the gap by considering a range of issues related to the history of the research of the site and its general context,
the study of the typological, technical, and technological parameters of the stone inventory, as well as determining the place of
Iskorost in the Stone Age of Ukrainian Polissia.
All artefacts of the site are made of local flint. There are 265 items in the collection. Blades and flakes constitute 95%
(252 pieces) of the inventory. There is no doubt that all flaked and detached products are associated with one technology aimed at
knapping blades. V. Khvoika purposefully selected artefacts from the cultural layer. Despite this, the inventory contains products
of all main stages of the technological process: from the selection of raw materials and the preparation of precores to the formation
and correction of prismatic relief, as well as the knapping of blades from the flaking surfaces of the cores. The use of soft
active elements prevails at all stages of the reduction sequence. However, traces of the use of hard hammerstones are recorded
on flaked and detached products as well (especially in the first phases of precores formation).
In conformity with the available data, Iskorost could be a workshop site with a small content of retouched tools. At the same
time, V. Khvoika excavated only an insignificant area, which could only be the place of primary processing of flint at the site.
According to the geomorphological position of the site, the type of used raw materials, and the features of the technology, it
can be assumed that Iskorost belongs to the Final Palaeolithic sites of Ukrainian Polissia. The high blade index and intensity of
utilization of the working surfaces of the cores, which mainly have two beveled opposed platforms and a bidirectional type of
knapping, the technical, morphological, and metric parameters of the flaked and detached products (including a high percentage
of willow-leaf blades among the blades from the working surfaces of the cores), the features of the preparation of the fracture
zone make it possible to refer Iskorost to the Swiderian industries.